Capital Flows in European Union on the Basis of International Investment Position – Selected Aspects - Maciejczyk-Bujnowicz, Iwona (Copernican Journal of Finance & Accounting, 2016)
The paper aims at assessing the changes in flows of selected forms of capital under deepening financial integration in the European Union. EU Member States are divided into two groups: members of the euro area and those outside of it. The analysis coincides with the establishing of the EU monetary union and covers the turn and early 21st century. Research method applied in this particular study includes the overview of theoretical concepts, literature review and a comparative statistical analysis based on statistical data. Analyses of selected data revealed significant differences between developed and developing countries when it comes to various forms of net capital and its relation to the GDP based on the International Investment Position. Moreover, we evaluated the International Investment Position of Poland against the backdrop of selected countries of Central and Eastern Europe and the eurozone members.